THE ILLUSION OF LIQUIDITY: WHY AMERICAN SMEs ARE FAILING DESPITE ACCESS TO CAPITAL AND HOW PREVENTION CAN REVERSE THE TREND - de Sousa Manfredi Cedini, Daniele (Revista Gênero e Interdisciplinaridade, 2026)
American small and medium-sized enterprises (SMEs) face a structural paradox: despite record volumes of capital made available through government programs such as the U.S. Small Business Administration (SBA) 7(a) Loan Program, bankruptcy rates continue on a sharp upward trajectory, particularly under Subchapter V of Chapter 11 of the U.S. Bankruptcy Code. This article presents a systematic literature review covering publications from 2020 to 2025, articulating empirical and conceptual evidence to explain why access to credit, disconnected from rigorous cash flow management and robust internal controls, frequently accelerates insolvency rather than preventing it. Using a PRISMA-based review protocol, studies from scientific databases, Federal Reserve reports, SBA data, and American Bankruptcy Institute (ABI) statistics were analyzed. Results reveal that the primary causes of SME failure lie not in capital scarcity but in managerial inability to monitor solvency indicators, manage operational cash flow, and implement effective internal controls. The article proposes a structured financial resilience framework, transforming financial management from a reactive activity into a proactive strategy for survival and sustainable growth.